2002
DOI: 10.1046/j.1442-2026.2002.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Blunt carotid artery injury

Abstract: Blunt carotid artery injury is an uncommon injury with a potentially devastating outcome. Although treatment is often unhelpful for an established neurologic deficit, there is frequently a delay between the episode of trauma and the onset of neurology. This delay provides a window of opportunity where early detection and intervention may significantly improve outcome and prevent lifelong morbidity in a generally young trauma patient population. This paper will review the literature regarding incidence, outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…A review of the literature done in 2002 showed a combined moderate and severe permanent neurologic deficit approximating 25 to 40% in survivors. 17 Mortality varies from 15 to 40%. Patients with an ipsilateral ischemic deficit on CT of the brain suffered a mortality of 47%, whereas mortality was 0% in those with a normal CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature done in 2002 showed a combined moderate and severe permanent neurologic deficit approximating 25 to 40% in survivors. 17 Mortality varies from 15 to 40%. Patients with an ipsilateral ischemic deficit on CT of the brain suffered a mortality of 47%, whereas mortality was 0% in those with a normal CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…10 Symptoms in the awake patient include head or neck pain (75% of cases) or ipsilateral Horner's syndrome (50% of cases), but the onset of symptoms can vary between hours and weeks after carotid artery injury. 12,13 In the multiply injured and anesthetized patient, symptoms are usually absent or masked. Only specific screening examinations may lead to early diagnosis before the occurrence of cerebral ischemia or stroke.…”
Section: E70mentioning
confidence: 98%
“…For extracranial ICA blunt injury, there are several classifications, such as the Biffl scale, Borgess classification, and Seth supplemental classification to Biffl [24][25][26][27].…”
Section: Classification and Gradingmentioning
confidence: 99%
“…However, for blunt carotid arterial injuries, the Borgess classification is limited. Currently, the Biffl et al scale is commonly utilized to assign vascular injuries and has become the standard for extracranial ICA blunt injury, from grade I to V as follows: grade I, irregularity or dissection with <25% stenosis; grade II, dissection with >25% luminal narrowing or a raised intimal flap; grade III, pseudoaneurysm; grade IV, complete occlusion; and grade V, ICA transection, active contrast extravasation [25,26].…”
Section: Classification and Gradingmentioning
confidence: 99%